State takeover legislation and share values: The wealth effects of Pennsylvania's Act 36 - Karpoff, Jonathan M.; Malatesta, Paul H. (Journal of Corporate Finance, 1995)
Proponents of state antitakeover legislation argue that previous empirical tests by financial economists of the wealth effects of Pennsylvania's 1990 antitakeover law are biased. We show that the proponents are correct. In particular, firm size, event-time clustering, and non-synchronous trading effects account for the wealth decreases reported in earlier studies. We also show, however, that both proponents and critics of the Pennsylvania legislation have ignored the earliest press release about it. The wealth effect associated with this announcement is negative, large, and statistically significant. These results therefore are consistent with the hypothesis that the Pennsylvania law decreased company values and with the hypothesis that the initial market reaction is an unbiased estimate of the law's effect on firm values.